LEGAL PROTECTION FOR THE WEAKER PARTY IN CIVIL CONTRACTS: A COMPARATIVE ANALYSIS OF INDONESIAN LAW AND INTERNATIONAL PRACTICE - Muhammad Yunus Idy; Abdul Rauf (Adisam Publisher, 2026)
Civil contracts, as fundamental instruments in modern legal and economic transactions, are often characterised by an imbalance in bargaining power between the parties, whereby the weaker party (consumers, workers, debtors) is in a vulnerable position and susceptible to contractual exploitation by the stronger party (business operators, employers, creditors). This study aims to analyse legal protection for weaker parties in civil contracts in Indonesia, compare it with international practices, and formulate policy recommendations to strengthen the national legal system. It employs a literature review using a legal-normative and comparative approach. The research findings indicate that Indonesia possesses a fairly comprehensive normative framework through the Civil Code and sectoral legislation; however, its effectiveness is hampered by low legal literacy, weak enforcement, and limited access to justice. Comparative analysis reveals that the European Union, the United States, and the United Kingdom have developed more advanced protection mechanisms, including mandatory protection that cannot be overridden by choice-of-law clauses, collective enforcement through consumer organisations and public authorities, and judicial flexibility to set aside unfair terms through the doctrine of unconscionability and the reasonableness test. This study recommends holistic reforms encompassing the adoption of the principle of mandatory protection, strengthening the powers of the BPSK and OJK for preventive oversight, integrating more flexible doctrines for the courts, simplifying class action mechanisms, and implementing a massive legal literacy programme. Without synergy between robust regulation, consistent enforcement, and community empowerment, legal protection for the vulnerable will remain a normative promise incapable of altering the reality of structural injustice in contractual relationships.